The behaviour of imports in Cameroon: An analysis through the equilibrium and disequilibrium models - NGONGANG, Elie (Journal of Economics and Political Economy, 2019)
Abstract. We have attempted, in this paper, to evaluate the structure and determinants of the demand for imports in Cameroon at the aggregated and disaggregated levels, using an equilibrium and disequilibrium models. It emerges from econometric estimation that real income, the real exchange rate and the variable capacity to importand industrialization were the determining factors in Cameroon imports. The degradation of imports illustrates the elastic or inelastic nature of imported products. Cameroon must reshape her development strategies towards industrialization in order for them to achieve a progressive reduction of their imports. This imperative situation would be a means that cannot be ignored by the Cameroon if it wants to attract foreign direct investment which is a source for the development of firms and for boosting productivity. Keywords. Structure, Imports, Development of firms, Industrialization, Cameroon. JEL. C20, F20, F30.